2020
DOI: 10.1080/26415275.2020.1744443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceramic material type on the fracture load of inlay-retained and full-coverage fixed dental prostheses

Abstract: Objective: Ceramic inlay-retained fixed partial denture (IRFPD) is a conservative prosthetic option but the mechanical durability of new high strength zirconia reinforced glass ceramic FPDs is not investigated. The purpose of this study was to compare fracture load of 3-unit ceramic FPDs. Materials and methods: Extracted premolars and molars (N ¼ 64) were used to create three test groups (IRFPDs) and one control group (full coverage FPD) (n ¼ 8). The teeth were embedded in PMMA resin with a mesiodistal distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
(59 reference statements)
0
4
2
Order By: Relevance
“…They related their results to the mechanical properties of zirconia, and the stiffness of the metal abutment used in their study, because of the different modulus of elasticity of Co-Cr alloy (180-240 GPa), compared to natural teeth (50-85 GPa for enamel, and 15-20 GPa for dentin). Contrary to our results, Kermanshah et al (2020) (20) and Mohsen et al (2010) (21) reported lower fracture resistance of monolithic zirconia IRFPDs. Kermanshah et al attributed this significant variation in results to the box shaped cavity preparation design since limited surface area was available for bonding, compared to occluso-proximal box preparation.…”
Section: Results Of Mz Group Were Comparable To Mehl Et Al (2010)contrasting
confidence: 99%
“…They related their results to the mechanical properties of zirconia, and the stiffness of the metal abutment used in their study, because of the different modulus of elasticity of Co-Cr alloy (180-240 GPa), compared to natural teeth (50-85 GPa for enamel, and 15-20 GPa for dentin). Contrary to our results, Kermanshah et al (2020) (20) and Mohsen et al (2010) (21) reported lower fracture resistance of monolithic zirconia IRFPDs. Kermanshah et al attributed this significant variation in results to the box shaped cavity preparation design since limited surface area was available for bonding, compared to occluso-proximal box preparation.…”
Section: Results Of Mz Group Were Comparable To Mehl Et Al (2010)contrasting
confidence: 99%
“…It should be affirmed that the values of fracture load seen in this study were more than those corresponding to a normal adult forces of occlusion, which differ from 190-290 N (in the anterior teeth) to 200-360 N (in the posterior region) [23]. Finally, the results of this study might be directly related to the materials/ methodology utilized and might not reflect what could happen under different circumstances.…”
Section: Resultscontrasting
confidence: 57%
“…The masticatory forces differed from 500 to 900 N in the posterior region and it was reported that posterior fixed partial dentures should withstand at least 500 N 3,4,16) . The fracture load results in this study ranged between 384 (Suprinity) to 931 N (TZI) in nonaged groups.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between two studies can be caused by differences in zirconia materials and designs of the restorations. Kermanshah et al 16) investigated the effect of ceramic material type on the fracture load of inlay-retained and full coverage fixed dental prostheses. Full coverage monolithic zirconia FPD, IRFPD made of monolithic zirconia, IRFPD made of monolithic zirconia internally coated by a porcelain layer, and IRFPD made of zirconia-reinforced lithium silicate were used to restore a maxillary second premolar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation